Potential biomarkers and molecular mechanisms in preeclampsia progression - Li Guohua; Huang Shijia; Liu Xiaosong; Du Qiaoling (Open Life Sciences, 2022)
This study aimed to explore potential biomarkers and molecular mechanisms in preeclampsia (PE) progression. Gene expression profiles of GSE147776 and GSE96984 were downloaded, followed by the identification of common differentially expressed genes (co-DEGs) and common differentially expressed lncRNAs (co-DElncRNAs) in PE patients between the two datasets. Key genes were identified using gene set enrichment analysis (GSEA), followed by functional enrichment analyses. Subsequently, the miRNAs of key genes and miRNA-related lncRNAs were predicted, followed by the construction of the lncRNA–miRNA–gene ceRNA network. Furthermore, the key genes associated with different gestational stages were identified. As a result, 192 co-DEGs and 16 co-DElncRNAs were revealed from the two datasets. Based on two outstanding PE-associated pathways, including glaucoma and PE, identified by GSEA, ten key genes, including IGFBP1, CORIN, and C3, were revealed. Key genes, including IL1A and IL1B, were enriched in the developmental process involved in reproduction. Furthermore, ceRNAs, such as LINC00473-miR-4476-IL1A, LINC00473-miR-1291-IL1B, and NAV2-AS4-miR-6131-REN, were identified. Moreover, REN expression was significantly upregulated in the first- and second-trimester placentae compared to C-section-term placentae. In conclusion, these key genes may serve as novel biomarkers for PE. The detection of REN expression may help in the early prediction of PE and the initiation of prophylactic medical treatment.